Improvement issue of information and analytical provision for electronic transparency implementation’s in professional bodies - Piliai, Ivan (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
In article was defined the approaches for improving the information and analytical provision of electronic transparency in prosecutor’s offices by means of: the definition and diversification of information technologies, services and products as special elements of information and analytical support that are used or should be implemented with the accompanying policies of prosecutor’s office informational awareness; substantiated proposals to the current legislation of prosecutorial activities concerning legal status unification of prosecutor’s offices web-infrastructure.